2023
DOI: 10.1371/journal.pone.0278670
|View full text |Cite
|
Sign up to set email alerts
|

The mother-to-child transmission of HIV-1 and profile of viral reservoirs in pediatric population: A systematic review with meta-analysis of the Cameroonian studies

Abstract: Background The mother-to-child transmission of HIV-1 (MTCT) remains on the major route of HIV-transmission among pediatric populations in Africa. Though a prevention of MTCT (PMTCT) high-priority country, data on the MTCT burdens in Cameroon remains fragmented. Objective We sought to assess the pooled MTCT rate, its risk-factors, and to characterize viral reservoirs of infected-children in Cameroon. Methods All relevant observational cohort and cross-sectional studies conducted in Cameroon were searched fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…With a goal to contribute and address one of the key research goals of the International AIDS Society Global Scientific Strategy 2021 and supporting efforts towards the elimination of AIDS as a pandemic by 2030, the present study provides insights into the quantitative characterization of total HIV-1 DNA in a typical SSA country like Cameroon. Given the framework of ART and the high burden of paediatric HIV-1 infection within this SSA setting, 30 it represents a unique land of opportunities for setting up baseline investigations that could pave the way for paediatric HIV-1 functional cure research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a goal to contribute and address one of the key research goals of the International AIDS Society Global Scientific Strategy 2021 and supporting efforts towards the elimination of AIDS as a pandemic by 2030, the present study provides insights into the quantitative characterization of total HIV-1 DNA in a typical SSA country like Cameroon. Given the framework of ART and the high burden of paediatric HIV-1 infection within this SSA setting, 30 it represents a unique land of opportunities for setting up baseline investigations that could pave the way for paediatric HIV-1 functional cure research.…”
Section: Discussionmentioning
confidence: 99%
“…The decay dynamics of HIV-1 DNA during early ART (within the first 12 weeks of life) in infants has been described previously, 41 , 42 , 43 , 44 reinforcing the need of very early ART initiation in a context where perinatal transmission of HIV-1 is still of concern. 30 Additionally, the CHER study has shown that a long duration on ART significantly decrease HIV-1 DNA levels in paediatric populations. 13 …”
Section: Discussionmentioning
confidence: 99%
“…In the absence of interventions, mother-to-child transmission of HIV ranges from 15% to 45%; in the non-breastfeeding population, this rate can be reduced to <2% with effective interventions during pregnancy and childbirth [12]. Despite the global success of PMTCT, some pregnant women with HIV are not diagnosed until the third trimester or even during childbirth, and so do not receive effective PMTCT interventions [13,14]. Hence, the growth and development of infants born to mothers with HIV and the genetic subtypes and drug resistance of infants with HIV deserves attention.…”
Section: Discussionmentioning
confidence: 99%
“…With the goal to contribute to the control of pediatric HIV-infection in the era of ART and to further support the UNAIDS agenda for research into a functional HIV cure in SSA, the present study has provided new insights on the expression of inflammatory (IL-1β, IL-6, IL-12, CCL2, CCL3, CCL4, IFNγ, IL-17A and TNFα), anti-inflammatory (IL-4 and IL-10), and inflammation-related (Il-6 and TGF-β1) cytokines/chemokines in APHI in a typical SSA setting like Cameroon. Taking into consideration the ART paradigm and the high burden of pediatric HIV-infection in SSA settings like Cameroon ( 4 , 9 ), this setting represents an ideal avenue for setting up baseline investigations that could pave the way for pediatric HIV cure research in this sub-region.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, sub-Saharan Africa (SSA) is paying the heaviest toll of pediatric HIV as ~85% of worldwide new pediatric infections occur in this region ( 2 ). Even though ART has substantially contributed to reducing HIV-1 MTCT ( 3 ), women in SSA settings (Cameroon included) ( 4 ) still face delayed HIV-1 diagnosis during pregnancy/breastfeeding, which leads to limited coverage in prevention of MTCT (PMTCT) and occurrence of new pediatric HIV-1 infections ( 5 ),…”
Section: Introductionmentioning
confidence: 99%